Implementasi Asas Peradilan Sederhana, Cepat, Adil, Mudah, Dan Murah Dalam Peradilan Administrasi - Nasarudin, Tubagus Muhammad (Universitas Malayati, 2024)
The principle of simplicity, speed, fairness, ease and low cost is a general principle found in the Indonesian judicial system, because this principle has been guaranteed in Law No. 14 of 1970 concerning the Main Provisions of Judicial Power. The principle of simplicity, speed and ease means that the trial procedure is formulated simply and easily understood and is not complicated. By being simple, easy, and reducing unnecessary formalities, it will produce a fast trial while still paying attention to the aspects of legal certainty and the value of justice. Low cost means a low cost that can be borne by the seeker of justice, especially the plaintiff. However, if the plaintiff is unable to pay the costs of the dispute, the plaintiff can submit an application to the Chief Justice to dispute at no cost. This is a convenience for citizens seeking justice in disputes in administrative courts. The principles of simplicity, speed, fairness, ease, and cheapness in administrative courts seem to be just wishful thinking in the eyes of the public (only a theory), surveys prove that what happens in the field is that this principle has not been fully implemented properly in the justice system in Indonesia, one of the causes is that there are too many procedures that must be gone through by justice seekers and the rampant corruption that occurs in the Indonesian courts so that the joints of justice are blocked which causes the loss of public trust in seeking justice.